Anaeromassilibacillus senegalensis gen. nov., sp. nov., isolated from the gut of a child with kwashiorkor. (July 2016) - Guilhot, E.; Tidjani Alou, M.; Diallo, A.; Raoult, D.; Khelaifia, S.
Abstract: We report the main characteristics of Anaeromassilibacillus senegalensis strain mt9 T (= CSUR P1511) isolated from the stool of a 1-year-old kwashiorkor patient from Senegal.